2011
DOI: 10.1530/jme-11-0094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single post-ovulatory administration of levonorgestrel on gene expression profile during the receptive period of the human endometrium

Abstract: The hypothesis that levonorgestrel (LNG) used as an emergency contraceptive interferes with endometrial receptivity remains unproven. We compared the endometrial gene expression profile during the receptive period after administering a single dose of LNG 1 . 5 mg or placebo on day 1 of the luteal phase. An endometrial biopsy was done on day LHC7 or LHC8 and samples were taken from seven volunteers, each one contributing with one cycle treated with placebo and another with LNG. The expression of 20 383 genes wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…In the present study, administration of MFP led to inhibition of genes involved in the processes of decidualization and implantation of the embryo, particularly of STAT3, in which the canonical signaling pathways ERK/MAPK, JAK/Stat, IL-15, and the acute phase signaling are shown to be associated with endometrial receptivity 20 . These observations agree with three previously published studies, in which the post-ovulatory administration of LNG did not change the expected pregnancy rate, nor the expression of genes involved in implantation 2,33,34 .…”
Section: A B Csupporting
confidence: 93%
“…In the present study, administration of MFP led to inhibition of genes involved in the processes of decidualization and implantation of the embryo, particularly of STAT3, in which the canonical signaling pathways ERK/MAPK, JAK/Stat, IL-15, and the acute phase signaling are shown to be associated with endometrial receptivity 20 . These observations agree with three previously published studies, in which the post-ovulatory administration of LNG did not change the expected pregnancy rate, nor the expression of genes involved in implantation 2,33,34 .…”
Section: A B Csupporting
confidence: 93%
“…Although our study was not designed to determine whether aberrant regulation of Maoa , Ednrb , and Hbegf gene expression reduces endometrial receptivity and blood flow in PCOS-like rats, our results combined with a clinical study indicating the beneficial effect of metformin on endometrial receptivity and blood flow in PCOS patients (Palomba et al, 2006) led us to speculate that metformin improves uterine receptivity and blood flow through the correction of aberrant Maoa , Ednrb , and Hbegf gene expression under hyperandrogenism and insulin resistance conditions and that this is important for the establishment of implantation and subsequent fertility. Indeed, several clinical studies have reported that endometrial MAOA and HBEGF expression is decreased in infertile women (Leach et al, 2012, Vargas et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Low doses of mifepristone administered daily or weekly in humans do not affect ovulation and fail to prevent pregnancy sufficiently although endometrial morphology and some of studied receptivity markers are affected [75,79,217]. Further, even well studied compounds such as LNG alter the gene expression in endometrium, although LNG does not adversely affect implantation [56,57,222,223].…”
Section: The Results From Study II and Iii In Contextmentioning
confidence: 99%